Strategic management of flood risk - McLuckie, Duncan; Kandasamy, Jaya; Sayers, Paul (ICE Publishing, 2018)
Strategic Management of Flood Risk offers a holistic approach for flood risk management to communities. This supports the practical consideration of the full range of flood behaviour in decisions that influence this risk. This book provides a logical framework and understanding of how flood risk to communities can be considered and managed. It discusses approaches that allow consideration of the variation of risk between and within floodplains, and across flood events of different scales. It investigates how land use planning activities that support community growth can be informed by an understanding of the variation in flood behaviour, flood function, and isolation of an area from safety, and the associated risks to the community and the built environment.